Development of Ultra-Carbon Steel Prepared by Mechanical Alloying and Subsequent Hot Pressing - Nurul T. Rochman; H. Sueyoshi (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2008)
It is known that the most effective way to improve mechanical properties of steels is by microstructural refinement. Iron and graphite powders mixture with hypoeutectoid composition were mechanically alloyed (MAed) and subsequently hot pressed (HPed) to provide steels with fine structure. Mechanical Alloying (MA) was carried out using a planetary ball mill for 100, 200 and 300 h, while HP at 41 MPa at various temperatures: 610ºC (below), 730ºC (near) and 800ºC (above the eutectoid transformation point A1). The mechanically alloyed (MAed) powders were characterized by X-ray diffraction (XRD), differential thermal analysis (DTA) and scanning electron microscopy (SEM). While, the HPed compacts were characterized by SEM, Vickers hardness and tensile test. During MA, refinement of crystallite, formations of super-saturated iron solid solution and Fe/C amorphous phase occured first. With further MA time, these phases might begin to transform to more stable phases such as carbides. In the case of HP at 610ºC (below A1), very fine cementites were precipitated in fine ferrite grain with sub-micron meter in the size. However, the mechanical properties cannot be attained because of low sinterability. At 730ºC (near A1), the strength reaches the maximum value. With further temperature increase (at 800ºC), the sintering progressed well and the coarsening occured, resulting the decrease in strength. However, the fracture strain increased significantly. The steels obtained in the present study had mechanical properties comparable to those of standard (JIS) steels through the welle stablished heat treatment such as normalizing and thermal refining.